Alcohol consumption and all-cause mortality: an analysis of general practice database records for patients with long-term conditions. Issue 8 (5th July 2017) - Stewart, Duncan; Han, Lu; Doran, Tim; McCambridge, Jim
Abstract : Background: Alcohol is a risk factor for ill health and reduced life expectancy, but little is known about the impact of alcohol on mortality for people with existing long-term conditions. We used primary care data from the Clinical Practice Research Datalink (CPRD) to study relationships between alcohol consumption and all-cause mortality among general practice patients with long-term conditions. Methods: Data were accessed from a sample of 125 general practices from the CPRD database. Adult patients with long-term health conditions, a record of alcohol consumption in CPRD and at least 1 year of follow-up data between 2000 and 2014 (n=95 991) were matched to the Office for National Statistics (ONS) mortality register. Results: In Cox proportional hazards regression models, mortality was higher for patients consuming 25–34 units of alcohol per week (HR 1.26, 95% CI 1.12 to 1.42) and 35 units or more (HR 1.71, 95% CI 1.51 to 1.94), compared with those drinking 1–7 units per week. Patterns of mortality risk were the same for men and women. Heavy drinking increased mortality risk in combination with smoking (HR 4.04, 95% CI 3.41 to 4.79) and high levels of deprivation (HR 3.01, 95% CI 2.40 to 3.79). Conclusions: Heavier drinkers with long-term conditions are at significantly greater risk of death than lighter drinkers. The findings support the UK Chief Medical Officers' guidance on having similar low-risk alcohol consumption guidelines for men and women. More needs to be done to tackle alcohol consumption among patients with long-term conditions.